RANCANG BANGUN PROTOTIPE PERANGKAT KERAS ELECTRIC VEHICLE SUPPLY EQUIPMENT MENGGUNAKAN PROTOKOL SAE J1772 - Liwa Purnadita, Putu Tesa; Rahardjo, Pratolo; Raka Agung, I G A Putu (Jurnal SPEKTRUM; Vol 11 No 2 (2024): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2024.v11.i02.p1, 2024)
The existence of Public Electric Vehicle Charging Stations (SPKLU) is increasing alongside the rise in electric vehicle usage in a certain area. EVCS is equipped with devices that directly interact with electric vehicles (EVs) during charging; this device is called Electric Vehicle Supply Equipment (EVSE). Both EVSE and EV require protocols to communicate with each other aimed at exchanging information such as readiness for charging between EVSE and EV. The communication protocol used in this research is the SAE J1772 protocol. This study focuses on designing a hardware prototype of EVSE based on the principles of the J1772 AC Type 1 connector as the transmission medium to electric vehicles (EVs). The design of EVSE communication simulation uses the Falstad Circuit Simulator platform, and the PCB layout design uses the EasyEDA platform. The hardware prototype of EVSE is controlled using a Raspberry Pi 3B mini PC as the core management, then integrated with the initial terminal block, power supply block, PZEM-004T sensor module, J1772 communication block, 2-channel solid-state relay (SSR) module, and J1772 terminal.